A new species of Physarum (Physaraceae) from Turkey - Eroğlu, Gönül (Phytotaxa, 2023)
A new species of Physarum, identified herein as P. karamanicum, developed on debris branches of Cedrus libani collected from the Sarıveliler district of Karaman province in Turkey and applied a moist chamber technique. P. karamanicum is morphologically similar to P. globuliferum, P. auripigmentum, and P. tenerum but is distinguished by sporotheca, stalk, capillitium, and spore features. The new species is characterized by a greenish-gray, globose sporotheca, light brown at the bottom, the remainder yellowish-cream colored stalk, triangular, convex quadrilateral nodes and pale-yellow capillitium, prominent spiny and groups of blunt warts spores, greenish gray peridium. Description of the new species, photographs (light microscope, stereo microscope, and scanning electron microscope), and a key to the closest morphologically related species of the genus are provided.